Characterisation of the dominant oxidative folding intermediate of hen lysozyme. - van den Berg, B; Chung, E; Robinson, C; Dobson, C (1999)
Reduced denatured lysozyme has been oxidised and refolded at pH values close to neutral in an efficient way by dilution from buffers containing 8.0 M urea, and refolding intermediates were separated by reverse-phase HPLC at pH 2. By using peptic digestion in combination with high-resolution Fourier transform ion cyclotron resonance (FT-ICR) mass spectrometry (MS) and tandem MS/MS the dominant intermediate was identified to be des-[76-94]. This species has three of the four native disulphide bonds, but lacks the Cys76-Cys94 disulphide bond which connects the two folding domains in the native protein. Characterisation of des-[76-94] by 2D1H NMR shows that it has a highly native-like structure. This provides an explanation for the accumulation of this species during refolding as direct oxidation to the fully native protein will be restricted by the burial of Cys94 in the protein interior.